An algebra problem by ابراهيم فقرا

Algebra Level 3

{ a + b + c = k a 2 + b 2 + c 2 = k a 3 + b 3 + c 3 = k a 4 + b 4 + c 4 = k \begin{cases} \begin{aligned} a\ + \ b\ +\ c \ & =k \\ a^2+b^2+c^2 & =k \\ a^3+b^3+c^3& =k \\ a^4+b^4+c^4 & =k \end{aligned} \end{cases}

If a , b , c , a,b,c, and k k satisfy the system of equations above, find the sum of all possible values of k . k.


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

If ( P i = x i + y i + z i ) (P_i=x^i+y^i+z^i)

According to Newton's identities,

P 4 = 4 P 3 P 1 3 P 2 P 1 2 + P 1 4 6 + P 2 2 2 P_4=\frac{4P_3P_1}{3}-P_2{P_1}^2+\frac{{P_1}^4}{6}+\frac{{P_2}^2}{2}

If P 1 = P 2 = P 3 = P 4 = k P_1=P_2=P_3=P_4=k , then we get the equation : k 4 6 k 3 + 11 k 2 6 k = 0 k^4-6k^3+11k^2-6k=0

The solutions of this equation are 0 , 1 , 2 , 3 0,1,2,3 , so the answer is 6 6

Chew-Seong Cheong
Dec 18, 2018

Relevant wiki: Newton's Identities

Let P n = x n + y n + z n P_n = x^n + y^n+z^n , where n n is a positive integer, S 1 = x + y + z = k S_1=x+y+z=k , S 2 = x y + y z + z x S_2 = xy + yz+zx , and S 3 = x y z S_3 = xyz . Given are P 1 = P 2 = P 3 = P 4 = k P_1=P_2=P_3=P_4=k . By Newton's sums or Newton's identities, we have:

P 1 = S 1 = k P 2 = S 1 P 1 2 S 2 = k 2 2 S 2 = k S 2 = k 2 k 2 P 3 = S 1 P 2 S 2 P 1 + 3 S 3 = k 2 k 3 k 2 2 + 3 S 3 = k S 3 = k 3 3 k 2 + 2 k 6 P 4 = S 1 P 3 S 2 P 2 + S 3 P 3 = k 2 k 3 k 2 2 + k 4 3 k 3 + 2 k 2 6 = k \begin{aligned} P_1 & = S_1 = k \\ P_2 & = S_1P_1 - 2S_2 = k^2 - 2S_2 = k & \small \color{#3D99F6} \implies S_2 = \frac {k^2-k}2 \\ P_3 & = S_1P_2 - S_2P_1 + 3S_3 = k^2 - \frac {k^3-k^2}2 + 3S_3 = k & \small \color{#3D99F6} \implies S_3 = \frac {k^3 - 3k^2+2k}6 \\ P_4 & = S_1P_3 - S_2P_2 + S_3P_3 = k^2 - \frac {k^3-k^2}2 + \frac {k^4-3k^3+2k^2}6 = k \end{aligned}

k 2 k 3 k 2 2 + k 4 3 k 3 + 2 k 2 6 k = 0 Multiply both sides by 6 6 k 2 3 k 3 + 3 k 2 + k 4 3 k 3 + 2 k 2 6 k = 0 k 4 6 k 3 + 11 k 2 6 k = 0 k ( k 3 6 k 2 + 11 k 6 ) = 0 k ( k 1 ) ( k 2 ) ( k 3 ) = 0 \begin{aligned} \implies k^2 - \frac {k^3-k^2}2 + \frac {k^4-3k^3+2k^2}6 - k & = 0 & \small \color{#3D99F6} \text{Multiply both sides by }6 \\ 6k^2 - 3k^3 + 3k^2 + k^4 - 3k^3+2k^2 - 6 k & = 0 \\ k^4 - 6k^3 + 11k^2 - 6k & = 0 \\ k(k^3-6k^2+11k-6) & = 0 \\ k(k-1)(k-2)(k-3) & = 0 \end{aligned}

Therefore, the sum of possible values of k k is 0 + 1 + 2 + 3 = 6 0+1+2+3 = \boxed 6 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...